Cytotoxic effects and anti-proliferative cancer activity of coelomic fluid from Lumbricus rubellus promotes apoptosis and reduces G2/M phase progression in HT-29 cells - Sofy Permana, Pearlindah, Zurniatus Sholihah, Agustin Iskandar & , Hani Susanti, Agustina Tri Endharti & (Journal of Applied Pharmaceutical Science, 2018)
This study has investigated the effect of chemotherapy drugs combined Coelomic Fluid (CF) derived from Lumbricus rubellus in HT-29 cells. HT-29 cells were treated with a combination of 5-fluorouracil (5-FU) (5 μg/ml) and Coelomic Fluid Lumbricus (CFL) (5 μg/ml, 10 μg/ml, or 20 μg/ml), respectively. The cells were incubated for 24 hours and then analyzed by flow cytometry to assess apoptosis, cell cycle progression, and proliferation. The cytotoxicity effect was measured by MTT assay that causes 50% decrease in cell viability (IC50 value). Results showed that the percentage of apoptosis in combined-therapy groups significantly higher than 5-FU single therapy group (p < 0.001). Additionally, the percentage of proliferation and cell growth significantly inhibited of 5-FU and CFL combination groups (p < 0.001). However, cell cycle slightly reduced the percentage of G2/M phase. Our results showed that CFL inhibited cell proliferation that is strictly dependent on colon cancer. These findings suggest that CFL have cytotoxicity effect to inhibit cell growth, anti-proliferative activity and increased apoptosis against human colon cancer cells.
Keywords: Apoptosis, cell cycle, cell proliferation, cytotoxic effect, coelomic fluid, 5-FU.